Smoking, Smokeless Tobacco Consumption & Coronary Artery Disease – A Case Control Study - Rohit V, Ram; Trivedi , Atul V (National Journal of Community Medicine, 2012)
Background: Coronary artery disease (CAD) is a major cause of premature death and disability throughout the world. Tobacco use is an important and avertable cause of CAD. The use of tobacco is on the rise worldwide. Present study was carried out to study the role of tobacco consumption in the occurrence of Coronary artery disease. Materials and Methods: Present study was a hospital based paired matched case-control study, carried out at civil hospital, Ahmedabad. 135 newly diagnosed cases of coronary artery disease and 135 controls were studied after taking informed written consent. Data was analyzed by using Epi-info version 3.5.1 computer package, Chi -square test, Z test and Odds ratio was calculated. Results: Among the total 135 cases 70.4% were male and 29.6% were female, most of the cases (40%) were belongs to the age group of 51-60 years. Smokers and smokeless tobacco users were significantly higher among the cases as compared to controls. Significant association was also observed between current smokers, smokeless tobacco users and Coronary artery disease. Strong associations were also observed between frequency and duration of smoking with CAD. Conclusion: Tobacco consumption in any form is major aetiology behind the occurrence of CAD.